MANAJEMEN PENDIDIKAN DALAM PERSPEKTIF ALQUR’AN DAN AS SUNNAH - Anwar, Cecep; Tresnawati, Leni (THORIQOTUNA: Jurnal Pendidikan Islam, 2022)
This article aims to reveal how the views of the Qur'an and As-Sunnah on education management. This study uses qualitative research methods with the type of research being library research, namely research relating to reading, recording and managing materials used in activities related to research. The literature study used is sourced from primary data and secondary data. The primary data sources are from the books of commentary, while the secondary data sources are from books and journals and the opinions of several experts. In the Qur'an there are verses that have to do with management such as the word "Yudabbiru" which refers to the regulation of the universe by Allah SWT, then it can also be understood in the human function as the Khalifah (representative) of Allah as a leader to regulate and prosper Nature. Allah's creation. Likewise, there are verses related to the functions and principles of management, namely Planning, Organizing, Actuating, and controlling. The success of education is not only determined by the completeness of facilities and infrastructure, curriculum, syllabus, media and so on, but is also largely determined by the human resources who carry it out as managers or leaders Artikel ini bertujuan mengungkap bagaimana pandangan Al-Qur’an dan As sunnah tentang manajemen pendidikan. Penelitian ini menggunakan metode penelitian kualitatif dengan jenis penelitiannya adalah kepustakaan (library research) yaitu penelitian yang berkenaan dengan membaca, mencatat dan mengelola bahan-bahan yang digunakan dalam kegiatan yang berkaitan dengan penelitian. Studi pustaka yang digunakan bersumber pada data primer dan data sekunder. Sumber data primer dari kitab -kitab tafsir, sedangkan sumber data sekunder dari buku-buku serta jurnal dan pendapat beberapa ahli. Dalam Al-Qur’an terdapat ayat-ayat yang ada hubungannya dengan manajemen seperti kata “Yudabbiru” yang mengacu kepada pengaturan alam raya oleh Allah SWT, kemudian dapat pula dipahami dalam fungsi manusia sebagai Khalifah (wakil) Allah sebagai pemimpin untuk mengatur dan memakmurkan Alam ciptaan Allah SWT ini. Begitu juga ditemui ayat-ayat yang berkaitan dengan fungsi dan prinsip manajemen yaitu Planning, Organizing, Actuating, dan controlling. Keberhasilan pendidikan bukan hanya ditentukan oleh lengkapnya sarana dan prasarana, kurikulum, silabus, media dan sebagainya, tapi juga sangat ditentukan oleh sumberdaya manusia yang melaksanakannya sebagai manajer atau pimpinan